Telescopic Overdenture - Bibinagar, Ragini; Anam, Chandrasekar; Mamidi, Praveen; Saxena, Aarti; -, Gautam; Rathinam, Jothi (Journal of Orofacial Research, 2013)
Preventive prosthodontics includes procedures that delay or eliminate future prosthodontic problems. Earlier, patients presenting with poor periodontal health, total extraction followed by a complete denture treatment was considered as permanent solution for oral health care but there was no concept of overdentures. Advantages of overdentures are that they prevent residual ridge resorption, provide better stability, retention, good esthetics and proprioception. The aim of this paper is to present a patient with partially edentulous maxillary arch who was rehabilitated with a telescopic overdenture.